Variations in arterial sources and supply patterns to the human trigeminal ganglion with clinical significance - Ethan L. Snow; William Srinivasan; Annika Covington; Matthew Vilburn; Travis L. McCumber; William Thorell (Translational Research in Anatomy, 2024)
Introduction: Trigeminal ganglia (TG) are bilateral collections of cell bodies from the first-order pseudounipolar neurons in each trigeminal nerve. Branches of the internal carotid artery (ICA), middle meningeal artery (MMA), accessory meningeal artery (AMA), and superior cerebellar artery (SCA) have been known to supply the TG, but information about the prevalence and patterns of these vessels supplying the TG is limited despite their important clinical relevance to basicranial surgeries. The objective of this study is to investigate the arterial sources and supply patterns to the TG and discuss their clinical implications. Methods: Gross arterial sources and supply patterns were examined on 139 TG from 90 embalmed human cadavers from ethically approved anatomical donor programs. Select specimens were photographed, and color replacement was utilized to aid structure identification. Vascular histology was examined with light microscopy and photographed on one specimen for methods validation. Results: One hundred and one TG (72.7%) received arterial supply from a single source: 71 (51.1%) from ICA, 18 (12.9%) from AMA, and 12 (8.6%) from MMA. Thirty-seven TG (26.6%) exhibited two distinct arterial sources from ICA, AMA, or MMA in either anastomotic (n = 25; 18.0%) or dual-independent (n = 12; 8.6%) patterns. One TG (0.7%) received supply from ICA, AMA, and MMA in a complex pattern. No gross arterial supply from SCA was found. Conclusions: The TG is predominantly supplied by ICA (prevalence = 76.3%), though AMA and MMA also represent considerable contributions (31.7% and 20.1%, respectively) in various supply patterns. The TG arterial sources and supply patterns reported in this study should be considered when deliberating treatment of meningiomas, schwannomas, and dural arteriovenous fistulas within and around Meckel's cave.